Erythrocyte diagnosticum as used in revealingmalignant process - L. A. Savluchinskayа; I. A. Bakulin; A. A. Molodyk (Успехи молекулярной онкологии, 2017)
A method is proposed for the development of an erythrocyte diagnosticum based on the evidence of patent № 2452501 (10.06.2012) via development of sensitine obtained from the serum of mares in foal, the above factor being used for diagnosis of malignant neoplasms. In order  to reveal the practical significance of the diagnosticum proposed the findings of the testing of the blood serum of 215 patients with variously located tumors and from 67 individuals without malignant tumors are analyzed. Sensitivity of the method was 88 %, specificity – 89 %,  accuracy – 89 %. The accessibility of the method proposed and simplicity of the reaction as well as the rapid response make it possible to use the method under discussion in any medical institution individually or in the course of screening to obtain primary diagnosis or to reveal risk groups.